ANALISIS IMPLEMENTASI PROGRAM ASI EKSKLUSIF DI PUSKESMAS SERING KECAMATAN MEDAN TEMBUNG - Fitriani Pramita Gurning; Chika Ismauzi Alfazira; Putri Hairuna; Yustika Anggraini Hasibuan (Jurnal Kesehatan Masyarakat (Undip), 2021)
Exclusive breastfeeding is the best type of initial food for babies and up to 2 months of age. The low coverage of exclusive breastfeeding in the working area of the health center, often in Medan Tembung sub-district, is around 67 babies (35%) who are given exclusive breastfeeding out of 191 babies, influenced by lack of participation from the mother pregnant and breastfeeding mothers to the exclusive breastfeeding program at puskesmas frequently. Therefore, the implementation of the exclusive breastfeeding program has become weak. The aim of this study was to determine the implementation of the exclusive breastfeeding program which included goals and objectives, the communication process (socialization), resources and characteristics of the program implementing agency. This method of research is effective. The research informants were 1 head of the puskesmas, 2 people in charge of the exclusive breastfeeding program, and 3 midwives for health workers. Data collection was through in-depth interviews with key informants and informants on triangulation and observations. The results showed that the implementation of exclusive breastfeeding programs in puskesmas is generally less successful. The program was implemented mentoring during push-ups and testing in the posyandu project. Communication in the program does not achieve the goals and objectives. The implementation of an exclusive breastfeeding program can be effectively implemented by increasing the social activities associated with the program according to the plan and by providing a support program for the program.